A Survey of the General Public on Poultry Topics - McCrea , B.A.; Moyle, J.R.; Flores, J.; Timmons, J.; Zimmermann, N. (International Journal of Poultry Science, 2015)
The Delmarva Chicken Festival has had an educational exhibit organized by extension poultry specialists/veterinarians for 25 years. A three question survey of the general public was performed at the 64th and 65th Annual Festivals to determine how much of the educational material has reached the general public. The results indicate that extension outreach needs to continue on educating the public that hormones are not used in chicken feed; that there is not nutritional difference between brown-shelled eggs and white-shelled eggs; and that commercial poultry farmers are stewards of the environment that we all share.